Ethical Games: Toward Evidence-Based Guidance for Safeguarding Players and Developers - Hodent,C; Blumberg,F; Deterding,S (Games: Research and Practice, 2024)
As video games have moved to the mainstream of entertainment and popular culture, they also have given rise to new media fears. These span concerns for player welfare such as gaming addiction, negative effects of ‘screen time,’ gambling-like mechanics, dark patterns and questionable business practices, online toxicity, and extremism. Questions of game worker welfare are similarly making headlines, such as harassment, discrimination, or precarious and unhealthy working conditions. To sort warranted concerns from unwarranted moral panics, the first Ethical Games Conference, held in 2024, gathered the state-of-the-art of research on ethical issues in games to inform evidence-based guidelines for industry and regulators. The selected full papers and opinion pieces of the conference, collected in this special issue, showcase a wide range of issues and barriers, and aspirations to move from avoiding harm to using games for positive social impact.